A systematic review and meta-synthesis of the qualitative research into mandatory personal psychotherapy during training - Murphy, David; Irfan, Nisha; Barnett, Harriet; Castledine, Emma; Enescu, Lily (Wiley, 2018)
Background: This study addresses the thorny issue of mandatory personal psychotherapy within counselling and psychotherapy training. It is expensive, emotionally demanding and time-consuming. Nevertheless, proponents argue that it is essential in protecting the public and keeping clients safe; to ensure psychotherapists develop high levels of self-awareness and gain knowledge of interpersonal dynamics; and that it enhances therapist effectiveness. Existing evidence about these potential benefits is equivocal and is largely reliant on small-scale qualitative studies.